Epistemologi Hadis dalam Pemboeka Pintoe Soerga Karangan Syeikh Haji Abdullah Ahmad - Rafika, Alfiah; Saputra, Doni; Yasti, Suci Amalia; Wendry, Novizal (Jurnal Riset Agama, 2023)
The article aims to examine the style of use and validity of hadith by Abdullah Ahmad in his book Pemboeka Pintoe Soerga. This research uses a qualitative method, by describing the data obtained descriptively from the book Pemboeka Pintoe Soerga, namely the traditions that Ahmad raises in his book. To test the validity of the traditions, the author used the method of takhrij hadith by tracing them in the hadith master books and books of takhrij hadith. This research proves that Abdullah Ahmad is not careful in using hadith. This is evidenced by the fact that the traditions presented by Ahmad are not equipped with the sanad and the source of the hadith narration, and there are also errors in the wording of the traditions he contains. In terms of quality, the traditions used by Ahmad in his book are sahih, dhaif and also the redactions that are said by Ahmad to be traditions, but the redactions are not traditions but the words of Ali ibn Abi Talib which are also considered by the Shiites as traditions.